Development of A Project Based Learning Model Based on Local Cultural Literacy to Improve Students' Critical Thinking Abilities - Zuhranis Dachrud; Arismunandar; Ansar (Jurnal Teknologi Pendidikan, 2025)
This study aims to develop a Project-Based Learning (PjBL) model based on local cultural literacy that meets the criteria of validity, practicality, and effectiveness in improving students' critical thinking skills in Indonesian language learning at the junior high school level. The background of this study is based on the low critical thinking skills of students, which are still influenced by the dominance of conventional learning that is textual in nature, lacks context, and does not optimally utilize the potential of local culture as a meaningful learning resource. In fact, Indonesian language learning has great opportunities to integrate local cultural values in the development of higher- order thinking skills.The results showed that the PjBL learning model based on local cultural literacy had excellent validity and practicality based on expert assessments and positive responses from teachers and students. The effectiveness test also showed a significant increase in students' critical thinking skills after the implementation of the learning model, with N-Gain scores in the moderate to high category. These findings indicate that the integration of PjBL with local cultural literacy is capable of creating contextual, meaningful Indonesian language learning that is oriented towards strengthening critical thinking skills, while also supporting the implementation of the Merdeka Curriculum and strengthening the Pancasila Student Profile.